Scattering‐Based Light‐Sheet Microscopy for Rapid Cellular Imaging of Fresh Tissue. Issue 6 (1st December 2020) - Nguyen, Christopher D.; O'Neal, Patrick K.; Kulkarni, Nachiket; Yang, Eric; Kang, Dongkyun
Abstract : Background and Objectives: Light‐sheet microscopy (LSM) is a novel imaging technology that has been used for imaging fluorescence contrast in basic life science research. In this paper, we have developed a scattering‐based LSM (sLSM) for rapidly imaging the cellular morphology of fresh tissues without any exogenous fluorescent dyes. Study Design/Materials and Methods: In the sLSM device, a thin light sheet with the central wavelength of 834 nm was incident on the tissue obliquely, 45° relative to the tissue surface. The detection optics was configured to map the light sheet‐illuminated area onto a two‐dimensional imaging sensor. The illumination numerical aperture (NA) was set as 0.0625, and the detection NA 0.3. Results: The sLSM device achieved a light sheet thickness of less than 6.7 µm over 284 µm along the illumination optical axis. The detection optics of the sLSM device had a resolution of 1.8 µm. The sLSM images of the swine kidney ex vivo visualized tubules with similar sizes and shapes to those observed in histopathologic images. The swine duodenum sLSM images revealed cell nuclei and villi architecture in superficial lesions and glands in deeper regions. Conclusions: The preliminary results suggest that sLSM may have the potential for rapidly examining the freshly‐excised tissue ex vivo or intact tissue in vivo at microscopic resolution. Further optimization and performance evaluation of the sLSM technology will be needed in the future. Lasers Surg. Med. © 2020 Wiley Periodicals LLC